Esperance - Oyebanji, Adam (DAW book collectors, 2025)
"A whip-smart thriller in the vein of Blake Crouch, Andy Weir, and Neal Stephenson, Esperance plumbs the depths of a seemingly impossible crime rooted in racism, intergenerational trauma, and an inhuman concept of justice"--